Exploring Viewing Skills Among Higher Education Students - Huri, Daman; Mulyati, Yeti; S. Daimaianti, Vismaia; Sastromiharjo, Andoyo (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to describe and identify viewing skills through multimodal analysis. This is motivated by the fact that in Indonesia, viewing skills are considered a new language skill. So that information is needed on how the ability of these skills is theoretically and practically. The approach used in this research is descriptive qualitative. This research used a population of Indonesian students with a sample of 145 students from the five largest islands. Data were obtained using questionnaires and multimodal analysis assignments. Data collection by distributing questionnaires and assignments to students, while data analysis uses descriptive statistical analysis and qualitative analysis. The results of the research can be identified that students have understood the concept of visual literacy, and with multimodal analysis, students are able to understand the meaning contained in the image. In addition, this research can also ensure that the use of audiovisual and visual media can be used in every learning process.